THE EFFECT OF AUDIT FEE, AUDIT DELAY, AUDIT TENURE, AND AUDIT ROTATION ON AUDIT QUALITY: Case Study of Non-Cyclical Consumer Companies Listed on the Indonesia Stock Exchange 2021-2023 - Lilin Naravita; Sri Rahayu; Muhammad Gowon (International Journal of Economics, Business and Innovation Research, 2025)
Audit quality is an essential dimension of financial reporting credibility, particularly for public companies listed on the Indonesia Stock Exchange (IDX). The credibility of financial statements is reinforced by reliable external audits that assure stakeholders of the accuracy and fairness of reported information. This study explores the impact of audit fee, audit delay, audit tenure, and audit rotation on audit quality within Consumer Non-Cyclicals sector companies over the period 2021–2023. The study applies a quantitative approach using secondary data from 41 IDX-listed companies with 123 firm-year observations. Audit quality is measured through the use of Big Four auditors, while explanatory variables include audit fees, audit delays, audit tenure, and audit rotation. Logistic regression is employed to test both individual and joint effects of the variables. Findings suggest that audit fees and audit delay significantly affect audit quality, while tenure and rotation show no significant influence. Collectively, all four variables jointly influence audit quality. These results provide theoretical contributions to agency theory and practical implications for regulators, auditors, and firms.